Os impactos da lei complementar n° 123/2006 nos pregões eletrônicos da Universidade Federal do Paraná - Jankoski, Andréa Roseli Moreira Cruz (2016)
Supplementary Law No. 123 of December 14, 2006, brought in Chapter V a number of benefits and differentiated treatments that should be dispensed to small business access to government procurement. This research aimed to analyze the influence of this Law result of electronic trading sessions at the Federal University of Paraná in the period from 2005 to 2013 were carried out searches in the minutes of electronic trading sessions to identify the amount of winning micro and small enterprises of bidding contests, and to check the number of trading days containing items related to computer equipment, computer supplies and other miscellaneous computer equipment to analyze the percentage of economy these sessions provided to the coffers of the Federal University of Parana. The research methodology used for this survey was the case study and data collection instruments were searching for documents such as the minutes of the sessions and a questionnaire was applied to micro and small entrepreneurs who have won three or more electronic auctions the Federal University of Paraná from 2005 to 2013. As a result, it was found that the share of micro and small companies after the implementation of Complementary Law No. 123/2006 was 75.7% on average in the years studied. The economic efficiency index obtained through the participation of SMEs was 38.99%, 15.21% higher than the economic efficiency achieved with companies from other participants sizes of 26 trading sessions analyzed. It was established that the Supplementary Law brought benefits to micro and small businesses as incentives to the participation of micro and small enterprises in the trading sessions; innovation, modernization and ease of access to trading floors by microenterprises and small businesses; competitive advantage, and the possibility of competition with medium and large companies. It is concluded that the LC 123/2006 is an important tool for public policies to foster economic growth of micro and small businesses.